SnO2-isolated Pt3Sn alloy on reduced graphene oxide: an efficient catalyst for selective hydrogenation of CO in unsaturated aldehydes1. Issue 6 (27th June 2015) - Shi, Juanjuan; Zhang, Mengyuan; Du, Weichen; Ning, Wensheng; Hou, Zhaoyin
<x xml:space="preserve">Abstract</x> A pyramid shaped Pt3Sn/SnO2/rGO hybrid is highly active, selective and stable for the hydrogenation of the CO bond in unsaturated aldehydes to unsaturated alcohols under mild conditions.